If it's not what You are looking for type in the equation solver your own equation and let us solve it.
21+3(x-4)=4(x+15)
We move all terms to the left:
21+3(x-4)-(4(x+15))=0
We multiply parentheses
3x-(4(x+15))-12+21=0
We calculate terms in parentheses: -(4(x+15)), so:We add all the numbers together, and all the variables
4(x+15)
We multiply parentheses
4x+60
Back to the equation:
-(4x+60)
3x-(4x+60)+9=0
We get rid of parentheses
3x-4x-60+9=0
We add all the numbers together, and all the variables
-1x-51=0
We move all terms containing x to the left, all other terms to the right
-x=51
x=51/-1
x=-51
| 8/3=m/7 | | 2x+2+3=4-1 | | 5x2+2x-4=0 | | 5x2+2x | | 7(x-3)-8=-5(-4x+3)-3x | | 4^5x+12=6^3x | | 3x=56.000 | | 3r+8=14 | | 3x=36.000 | | 2(10-y)+y=15 | | 38x-288=0 | | 25/x+4=9 | | 1.50x=19=2.75x+15 | | 5(w-6)-4=-4(-6w+5)-7w | | 2(u-7)=-4u-38 | | 13x+16=3x+7 | | 20=3(y-5)-8y | | 0.8x+0.1x=3.6 | | 12(2x+11)=12(2x+11) | | (4z+3)(8+z)=0 | | 7x+14=4(x+2) | | x+37+49=180 | | X-(5-x)=1 | | s+5=16 | | 4(x+6)-6x=14 | | s+5=15 | | -2(v+9)=-7v-23 | | 3(w-7)-5w=-33 | | 5(u+4)-8u=11 | | -y+8=3y+14-10 | | -6u+20=4(u-5) | | x/7-10=-18 |